Inflammatory Mediators and Angiogenic Factors in Choroidal Neovascularization: Pathogenetic Interactions and Therapeutic Implications - Claudio Campa; Ciro Costagliola; Carlo Incorvaia; Carl Sheridan; Francesco Semeraro; Katia De Nadai; Adolfo Sebastiani; Francesco Parmeggiani (Mediators of Inflammation)
Choroidal neovascularization (CNV) is a common and severe complication in heterogeneous diseases affecting the posterior segment of the eye, the most frequent being represented by age-related macular degeneration. Although the term may suggest just a vascular pathological condition, CNV is more properly definable as an aberrant tissue invasion of endothelial and inflammatory cells, in which both angiogenesis and inflammation are involved. Experimental and clinical evidences show that vascular endothelial growth factor is a key signal in promoting angiogenesis. However, many other molecules, distinctive of the inflammatory response, act as neovascular activators in CNV. These include fibroblast growth factor, transforming growth factor, tumor necrosis factor, interleukins, and complement. This paper reviews the role of inflammatory mediators and angiogenic factors in the development of CNV, proposing pathogenetic assumptions of mutual interaction. As an extension of this concept, new therapeutic approaches geared to have an effect on both the vascular and the extravascular components of CNV are discussed.